Clinical and radiographic prospective study of customized one-piece titanium and one-piece fusion-sputtered zirconia implants: five-year mean follow-up - Mahy Hassouna; Walid Al-Zordk; Moustafa Aboshilib; Mohamed Ghazy (BMC, 2022)
Abstract Background To evaluate the clinical and radiographic assessment of customized fusion-sputtered one-piece zirconia implants. Methods Twenty-eight patients received either fusion sputtered one-piece zirconia implants (n = 14) or one-piece titanium implants (n = 14). All implants were one-piece designs. After 4 months of immediate loading, all implants were restored with a monolithic zirconia crown. All implants were evaluated at baseline, 6 months, 1 year, 2 years, and 5 years. Implant mobility, plaque index, and gingival index evaluations were performed. The measurements of marginal bone level were calculated radiographically. Results All implants were well maintained through the evaluation period with a 100% survival rate without any clinical complications. Regarding gingival index, there was no statistically significant difference (P = .364) between zirconia (3.3 ± 0.7 mm) and titanium (3.5 ± 0.6 mm) implants, after 5 years. There was no statistically significant difference (P = .470) between zirconia (1.77 ± 0.039 mm) and titanium (1.80 ± 0.28 mm) implants regarding marginal bone loss, after 5 years. Conclusions One-piece fusion-sputtered zirconia implant represents a reliable treatment modality in replacing a missing tooth in the esthetic zone.